Suomen terveysteknologia-alan nykytila ja haasteet - Mikko Grönlund; Reetta Raitoharju; Tuomas Ranti; Kaapo Seppälä; Tom Ståhlberg (Tekes – the Finnish Funding Agency for Innovation, 2022)
Suomen terveysteknologia-alan yritykset ovat sijoittuneet eri puolille maata painopisteen ollessa kuitenkin viidessä maakunnassa. Näille maakunnille on yhteistä, että niissä toimii yliopistollinen sairaala. Eniten terveysteknologia-alan yrityksiä toimii Uudellamaalla, Pirkanmaalla ja Varsinais-Suomessa. Valviran laiterekisterin yrityksistä kaksi kolmasosaa toimii näissä kolmessa maakunnassa. Seuraavaksi eniten yrityksiä toimii Pohjois-Pohjanmaalla sekä Pohjois- Savossa.
Puhuttaessa terveysteknologia-alasta nousevat usein esille nosteessa olevat startup-yritykset. Valviran laiterekisterin yritysten iän mediaani vuonna 2015 oli kuitenkin jo 17 vuotta (keskiarvo 18 vuotta) ja neljännes yrityksistä on perustettu ennen vuotta 1990. Noin joka seitsemäs rekisterissä olevista yrityksistä on perustettu vuonna 2010 tai sen jälkeen ja noin puolet vuosituhannen vaihteen jälkeen. Voidaankin sanoa, että ainakin terveysteknologian alan ytimen muodostavien Valviran laiterekisterin yritysten liiketoiminta on yleistä käsitystä vakiintuneempaa.
Terveysteknologia-ala on, kuten useimmat muutkin toimialan Suomessa, varsin pienyritysvaltainen ja polarisoitunut. Noin joka neljännen yrityksen vuotuinen liikevaihto oli alle 0,2 miljoonaa euroa, ja puolella yrityksistä liikevaihto jäi alle miljoonan euron. Noin joka kahdeksannella yrityksellä liikevaihto oli 20 miljoonaa euroa, ja vain muutama yritys ylsi yli 100 miljoonan euron liikevaihtoon. Henkilöstömäärällä mitattuna yli puolet Valviran laiterekisterin yrityksistä oli mikrokokoisia, eli sellaisia, joiden työntekijämäärä on alle 10 henkeä. Alle 50 henkeä työllistävien yritysten osuus oli noin neljä viidesosaa. Suuryrityksiä eli vähintään 250 henkeä työllistäviä oli vajaat 6 prosenttia.
Terveysteknologia-alan yrityksistä selvästi yli puolet toimii kansainvälisillä markkinoilla ja loput ensisijaisesti valtakunnallisilla markkinoilla. Vain alueellisilla tai paikallisilla markkinoilla toimivien yritysten määrä on hyvin
The Finnish health technology companies, classified in this research as such through having at least one product registered in the National Supervisory Authority for Welfare and Health (Valvira) product register, are distributed around Finland, with an emphasis on regions with a university hospital. Most of the firms are based in Uusimaa, Pirkanmaa and Finland Proper. Of the companies in the Valvira register, two-thirds are based in these counties. The next largest number of health technology companies are located in North Ostrobothnia and Northern Savonia.
When discussing the health technology industry, startup firms are often mentioned. However, the median age of the companies in the Valvira register in 2015 was 17 years (average 18 years), and a quarter of the companies had been founded before 1990. Approximately one out of seven companies in the register had been founded in or after the year 2010, and approximately half after the year 2000. Therefore, it can be said that at least the business activity of the companies forming the core of the companies in the Valvira register is better established than commonly thought.
The health technology industry, as most other industries in Finland, is polarised, consisting mainly of small firms. In 2015, the yearly sales of approximately a quarter of the companies was under 0.2 million euro, and in half of the companies, under one million euro. Approximately one in eight companies had yearly sales of at least 20 million euro, and only a couple of companies reached yearly sales of over 100 million euro. In terms of the number of personnel, over half of the companies in the Valvira register were micro-sized, i.e. had fewer than 10 employees. Approximately four out of five companies employed fewer than 50 employees. The proportion of large companies, i.e. companies employing at least 250 people, was approximately 6 percent.
With regard to their internationalisation, clearly over half of the health technology companies are functioning on the international market and the rest primarily on the domestic market. There are only few companies operating merely on a local scale.
According to the balance sheet materials of the research, the health technology-related sales of the Valvira-listed 260 companies totals nearly 1.7 billion euro, with a total personnel of approximately 7200 employees. A larger group of 418 companies was recognised as focusing on health technology business, even though they did not necessarily produce medical devices, with aggregate sales in 2015 of approximately 2.1 billion euro, and a total personnel of over 10200 employees.
The median growth of sales of health technology companies has varied somewhat during the examined period. For instance, in 2009, the sales of the companies declined significantly with the median growth of sales sinking to -3.1%. After a growth period of two years, the median of sales growth sunk to 0 percent in 2013. On the other hand, it is worthwhile to notice that the growth of sales is not the only important issue, as profitability should also be considered while growing. In 2015, the median of sales growth of the health technology industry was 3.9%. However, there were major differences in the development of sales growth, as the sales of every fourth company grew over 20% in 2015, meanwhile the sales of every third company decreased.
The development of the net result, a measure of the profitability of the companies, has been rather steady. After 2012, the profitability of the companies has been in a slight decline, and in 2015 the median of net result was 2.1%, and over a third of the companies were making a loss. The profitability of the best quadrant was however very good, as the upper quartile of net result percentage in 2015 was over 10%. The risk of bankruptcy of health technology companies was on general level small. However, there are major differences in the risk of bankruptcy, and in a quarter of the companies the situation is challenging in that regard.